(untitled) (Transmediterranean History, 2024)
In its later versions, the collection of tales known as 1001 Nights contains “The Story of the Man from Upper Egypt and His Frankish Wife” (Ḥikāyat al-Ṣaʿīdī wa-zawǧatihi al-ifranǧiyya), whose earliest written evidence hails from the late thirteenth or early fourteenth century. The story as such unfolds in the Ayyūbid period between 1185 and 1207 and describes events that led up to and followed from the Battle of Ḥiṭṭīn. Its main protagonist is a flax merchant from Upper Egypt who falls in love with a Frankish woman from Acre and eventually marries her. The article describes the story’s historical setting and analyses its narrative patterns. Discussing to which degree a fictional text can provide insight into the historical realities of Ayyūbid Syria and Egypt, it comments on various issues that form part of the narrative, including slavery and captivity, romance and marriage, and different instances of interreligious communication.